MANAJEMEN PEMBELAJARAN TEMATIK INTEGRATIF SESUAI KURIKULUM 2013 PADA KELAS 4 SD KHADIJAH SURABAYA - Nafiah, Nafiah (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2017)
The purpose of this study is to describe the implementation of management of integrative thematic learning based on curriculum 2013 at grade 4 khadijah primary school Surabaya. The focus of this study are 1. The lesson plan for integrative thematic class based on curriculum 2013 at grade 4 khadijah primary school . the research method of this study is descriptive kualitatif, the data collection technique are interview, observation and documentation. The result of this study are 1) the lesson plan of integrative thematic based on curriculum 2013 at grade 4 khadijah primary school Surabaya conducted by several steps are : a) set thema, b) doing analisys SKL, KI, and basic competence, c) arrage syllabus, d) arrage the lesson plan, 2) doing integrative thematic learning based on curriculum 2013 at grade 4 Khadijah primary school used scientific approch by observing, questioning, reasoning, trying, processing, displaying, verivicaying, and communicating, 3) the assessment of integrative thematic learning based on curriculum 2013 at grade 4 khadijah primary school used authentic assessment that include written assessment, project assessment and portfolio assessment.